The in vivo effects of copper, manganese and mercury mixtures on the heart, lung and brain and the coagulation system in the Sprague-Dawley rat model - Oberholzer, Nanette (University of Pretoria, 2022)
Thesis (PhD (Anatomy))--University of Pretoria, 2021.